2009
DOI: 10.1016/j.bcp.2008.10.036
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 antagonistic peptides inhibit TGFβ1-dependent angiogenesis

Abstract: The role of transforming growth factor-beta (TGF) in tumor promotion and in angiogenesis is context-dependent. While TGF prevents tumor growth and angiogenesis in early phases of tumor development, evidence is accumulating about its pro-angiogenic and tumor promotion activities in late stages of tumor progression. Here we have studied, in an experimental context previously reported to disclose the pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 52 publications
2
39
0
1
Order By: Relevance
“…However, injection of anti-TGF-β and anti-TGF-βRI antibodies inhibits chronic synovial inflammation in rats with SCW-induced arthritis [38] and in CAIA mice [25]. In CIA, treatment with p17 TGF-β antagonist at the same doses shown previously to block activity of TGF-β in vivo [31,[39][40][41][42][43] did not prevent or modify the severity of the disease, neither during the induction phase nor during established arthritis. As Marinova-Mutafchieva et al have shown that TGF-β expression is induced in the joints at the time of arthritis onset, the time of treatment of CIA mice during clinical progression of disease is justified.…”
Section: Discussionmentioning
confidence: 99%
“…However, injection of anti-TGF-β and anti-TGF-βRI antibodies inhibits chronic synovial inflammation in rats with SCW-induced arthritis [38] and in CAIA mice [25]. In CIA, treatment with p17 TGF-β antagonist at the same doses shown previously to block activity of TGF-β in vivo [31,[39][40][41][42][43] did not prevent or modify the severity of the disease, neither during the induction phase nor during established arthritis. As Marinova-Mutafchieva et al have shown that TGF-β expression is induced in the joints at the time of arthritis onset, the time of treatment of CIA mice during clinical progression of disease is justified.…”
Section: Discussionmentioning
confidence: 99%
“…4 Whereas TGF-␤ often restricts tumor growth and angiogenesis in the early phase of tumor development, there is evidence for its proangiogenic and tumor-promoting activities during late-stage tumor progression. 43 TGF-␤-induced angiogenesis was linked to urokinase-type plasminogen activator receptor and its type 1 inhibitor up-regulation. 43 Furthermore, TGF-␤ was shown to up-regulate VEGF-C. 44 Our results suggest that both S1P and TGF-␤ are present in the CM AC and are needed for HIF-␣ mRNA expression regulation in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…43 TGF-␤-induced angiogenesis was linked to urokinase-type plasminogen activator receptor and its type 1 inhibitor up-regulation. 43 Furthermore, TGF-␤ was shown to up-regulate VEGF-C. 44 Our results suggest that both S1P and TGF-␤ are present in the CM AC and are needed for HIF-␣ mRNA expression regulation in macrophages. As neither TGF-␤ nor S1P alone or in combination was sufficient in inducing HIF-1␣, we assume that combinatory and thus more complex signaling circuits are operating.…”
Section: Discussionmentioning
confidence: 99%
“…P144 blocked TGF-β signaling and displayed potent inhibition of angiogenesis in several in vitro assays [131]. Phase I clinical trials have been completed and P144 is currently in phase II clinical trials sponsored by ISDIN in collaboration with DigNa Biotech, to assess efficacy and safety of topical application of P144 in the treatment of skin fibrosis in patients with systemic sclerosis [132].…”
Section: Tgf-β As Therapeutic Targetmentioning
confidence: 99%